Gender-related beliefs and attitudes about tobacco use and smoking cessation in Mexico - Rodríguez-Bolaños, Rosibel; Caballero, Marta; Ponciano-Rodríguez, Guadalupe; González-Robledo, Luz María; Cartujano-Barrera, Francisco; Reynales-Shigematsu, Luz Myriam; Cupertino, Ana Paula (Health psychology & behavioral medicine, 2021)
Background. While overall trends in tobacco use among men are declining, tobacco use continues to rise significantly among women in developing countries. This study aimed to explore the gender-related beliefs and attitudes about tobacco use and smoking cessation in Mexico, one of the top five Latin America countries with the highest prevalence of tobacco consumption. Materials and Methods. This study was conducted using an explanatory qualitative methods design. Semi-structured interviews were conducted with 14 adults smokers (8 women & 6 men) who visited primary healthcare clinics in Mexico City. Two researchers independently coded the interviews and applied the final codes upon consensus. Inter-rater reliability was assessed for four groups of codewords (92% agreement), based on an ecological model on socio-cultural factors. Findings. Initiation to smoking in women begins out of curiosity, and in men by imitation. Also, women start using tobacco at an older age compared to men. During maintenance of smoking, women report experiencing loneliness and anxiety about multiple responsibilities, e.g. women reveal that they feel guilty when they smoke due to their maternal role as caregivers. Additionally, some women report that smoking is a symbol of freedom, recalling the media messages associated with promoting tobacco products. Among men, the results show that they smoke for pleasure and to socialize, and consider that women smoke to imitate men and feel powerful. Regarding cessation, women are ambivalent about quitting smoking or not, and men mention not needing professional support. For organizational barriers, women mention the cost of treatment and men, the distance to clinics. Conclusion. Smoking cessation interventions should be proposed from an approach that involves changes in social norms, seeking a more equitable relationship between men and women. Therefore, there must be broad engagement from different sectors and not just at the health sector level.